ARTS mediates apoptosis and regeneration of the intestinal stem cell niche - Elle Koren (Nature Portfolio, 2018)
The mechanisms regulating intestinal stem cell elimination remain unclear. Here, the authors identify that the pro-apoptotic protein ARTS (a Septin4 isoform) interacts with XIAP in the intestinal stem cell niche to  regulate stem cell survival during intestinal homeostasis and regeneration.